Ecological Notes on the Thematode Parasites of Helisoma Anceps (Menke) in a Eutrophic Lake, Including a Check-List of the Cercariae That Occur on Mollusks Indigenous to Otsego County, New York - Theodore Katsigianis; Willard N. Harman (Hello World!, 1974)
A population of Helisoma anceps (Menke) was studied from June 1972 to June 1973 at the State University of New York College at Oneonta Biological Field Station, Cooperstown, Otsego County, New York. Monthly collections of snails were made to determine the species of larval trematodes developing within this particular host. Water temperature and pH were measured during each collection to determine their effect on the incidence of infection.